2021
DOI: 10.1371/journal.pone.0260350
|View full text |Cite
|
Sign up to set email alerts
|

Serum syndecan-1 concentration in hospitalized patients with heart failure may predict readmission-free survival

Abstract: Syndecan-1 is found in the endothelial glycocalyx and is released into the bloodstream during stressed conditions, including severe diseases such as acute kidney injury, chronic kidney disease, and cardiovascular disease. This study investigated the prognostic value of serum syndecan-1 concentration in patients with heart failure upon admission. Serum syndecan-1 concentration was analyzed in 152 patients who were hospitalized for worsening heart failure from September 2017 to June 2018. The primary outcome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The endothelial glycocalyx, a gel-like layer of glycoproteins that covers the luminal surface of the capillary endothelium, is thought to maintain organ and vascular homeostasis ( 7 ). Syndecan-1 (SDC-1), the core protein in heparan sulfate proteoglycan, is found in the endothelial glycocalyx and shed into the blood in various systemic inflammatory conditions, including trauma ( 7 , 8 ), sepsis ( 9 ), acute respiratory distress syndrome ( 10 ), acute kidney injury ( 11 ) and cardiovascular disease ( 12 , 13 ). Additionally, several studies have demonstrated an association between serum SDC-1 level and mortality in trauma patients ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The endothelial glycocalyx, a gel-like layer of glycoproteins that covers the luminal surface of the capillary endothelium, is thought to maintain organ and vascular homeostasis ( 7 ). Syndecan-1 (SDC-1), the core protein in heparan sulfate proteoglycan, is found in the endothelial glycocalyx and shed into the blood in various systemic inflammatory conditions, including trauma ( 7 , 8 ), sepsis ( 9 ), acute respiratory distress syndrome ( 10 ), acute kidney injury ( 11 ) and cardiovascular disease ( 12 , 13 ). Additionally, several studies have demonstrated an association between serum SDC-1 level and mortality in trauma patients ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that syndecan-1 may reflect vascular capacitance load 23 . Conversely, ANP secretion is stimulated by atrial muscle stretch due to atrial pressure, while BNP is secreted when a ventricular load is applied 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The criticism argues that more event data and tougher criteria are required for strong prediction capability [103]. Furthermore, the discussion emphasizes the necessity of taking into account the interaction between various serum biomarkers and incorporating validated biomarkers for cardiovascular disease when estimating the mortality risk in patients with heart failure, suggesting that a larger dataset is necessary for precise analysis [104,105].…”
Section: Estimation Of Endothelial Glycocalyx Damage In Heart Surgica...mentioning
confidence: 99%